Point-defect management in homoepitaxially grown Si-doped GaN by MOCVD for vertical power devices. (1st May 2022) - Rathkanthiwar, Shashwat; Bagheri, Pegah; Khachariya, Dolar; Mita, Seiji; Pavlidis, Spyridon; Reddy, Pramod; Kirste, Ronny; Tweedie, James; Sitar, Zlatko; Collazo, Ramón
Abstract: We demonstrate controlled Si doping in the low doping range of 5 × 10 15 –2.5 × 10 16 cm −3 with mobility >1000 cm 2 V −1 s −1 in GaN films grown by metalorganic chemical vapor deposition. The carbon-related compensation and mobility collapse were prevented by controlling the electrochemical potential near the growth surface via chemical potential control (CPC) and defect quasi-Fermi level (dQFL) point-defect management techniques. While the CPC was targeted to reduce the net CN concentration, the dQFL control was used to reduce the fraction of C atoms with the compensating configuration, i.e. C N − 1 . The low compensating acceptor concentration was confirmed via temperature-dependent Hall effect analysis and capacitance–voltage measurements.